How do political coups disrupt Fiji's tourism? Impact assessment on ecotourism at Koroyanitu National Heritage Park (KNHP), Abaca. Issue 5 (May 2021) - Kundra, Sakul; Alam, Mumtaz; Alam, Mohammad Afsar
Abstract: The nexus between mass tourism and politics has been widely validated in tourism literature; nonetheless, the impacts of political putsches on ecotourism are understudied in the context of the Pacific Islands, i.e., Fiji. This study aims to investigate how Fiji's political upheavals impacted ecotourism after examining ecotourist arrivals and revenue generated at KNHP from its inception till 2018. Additionally, it presents a comparative analysis of Fiji coups on tourism and ecotourism and examines the recovery pattern of ecotourism in the post-coup stage. The study implies both empirical and non-empirical methods. This research is based on field visits to the Abaca ecotourism project, Lautoka, from 2017 to 2019, and has employed quantitative data of Abaca's tourist revenue records; supplemented by conducting oral unstructured interviews of the Abaca project manager through talanoa sessions. The collected data were analyzed using Microsoft Excel 2010 and STATA and Augmented Dickey Fullar (ADF) test to check the stationarity. The research has defied the antecedent arguments of the failure of ecotourism projects in Fiji and made a first-ever comparative analysis of ecotourism data with mass tourism in relation to post-coup recovery tenure. It postulates an apparent correlation of the success of this ecotourism park with the democratically elected government of Fiji. The Abaca ecotourist park displayed potential to emerge as an ecotourism hub in the entire South Pacific, provided the democratically elected government could sustain in Fiji, which has been tagged as 'coup-coup land'. Henceforth, this study can be replicated for similar destinations in the world. Abstract : Coups, Democratic government, Ecotourism, Fijian nationalism, Political impact, Post-coup recovery, KNHP, Fiji.